Asymmetry of affect in verbal irony understanding: What about the N400 and P600 components?. (August 2019) - Caillies, Stéphanie; Gobin, Pamela; Obert, Alexandre; Terrien, Sarah; Coutté, Alexandre; Iakimova, Galina; Besche-Richard, Chrystel
Abstract: We investigated the neurocognitive processes behind the asymmetry of affect observed in irony understanding, where ironic criticism is more easily understood than ironic praise. We recorded the ERPs of participants while they listened to positive (e.g., "These children are always smiling") or negative (e.g., "His son is very unfortunate") remarks pronounced with a sincere or ironic prosody. Participants had to decide whether or not the speaker was sincere. Behavioural results confirmed the asymmetry of affect phenomenon and ERP results revealed that the N400 and P600 were differentially sensitive to the negative or positive emotional connotations of the speaker's messages. These findings shed new light on the cognitive processes behind biphasic N400/P600 cycles, and how they are differentially affected by negativity. Highlights: We examined the neurocognitive processes behind auditory verbal irony processing. We examined these processes via two event-related brain potentials: N400 and P600. N400 and P600 were differentially sensitive to the ironic final adjective's valence. Prosody is immediately used as a cue.